Hubungan antara budaya formal sekolah dan gaya pembelajaran pelajar dengan pencapaian akademik pelajar sekolah menengah - Yahaya, Azizi (2011)
The purpose of this study is to identify the relationship between formal school culture and student’s learning styles with academic achievement. The sample consists of 234 students from five secondary schools in Pontian, Johor. The sampling has been done using the cluster on cluster random sampling method. The pilot study was done in order to determine the reliability and suitability of the questionnaires. Meanwhile Cronbach Alpha was used to determine the internal consistency of the questionnaires. The reliability value of Cronbach Alpha for the whole set of questionnaires used was 0.953. The questionnaire for formal school culture was adapted and modified from climate or culture in formal school form constructed by Curriculum Development Centre (1988). The questionnaire for student’s learning styles was adapted and modified from Barbe Modality Index questionnaire that was created by Barbe (1985). Descriptive statistics sush as frequency, mean and standard deviation were used to analyse the dominant aspects of formal school culture and student’s learning styles and to analyse student’s academic achievement. The inferential statistics such as Pearson correlations were used at significant level 0.05 to analyze the relationship between formal school culture and student’s learning styles with academic achievement. In addition, t-test was used to analyze the difference between formal school culture and student’s learning styles toward school location. The findings from this study showed that the dominant aspect of formal school culture was social. The results showed that the dominant aspect of students’ learning style was visual. Pearson correlation analysis showed that there was significant relationship between formal school cultures with academic achievement. Moreover, there was significant relationship between student’s learning style with academic achievement. Therefore, suggestions were made in this study. The study suggested that teacher and student should identify formal school culture and student’s learning styles, so that, student can increase their academic performance